The Role of Management Control in The Implementation of Objectives and Tasks in The Health Care Sector in Poland - Dariusz KOTARSKI (Communications of International Proceedings, 2024)
The aim of the study is to determine the role of management control in the implementation of objectives and tasks for the development of the health care sector, taking into account legal, financial, executive and reporting regulations. The paper uses a method of analysis of documentation in the field of the applied management control policy, statements on the state of management control of the Minister of Health, activity plans and reports on the implementation of the activity plan of the Minister of Health for the government administration department: Health in 2018–2022. The paper presents current objectives (also included in the activity-based budget), tasks and measures of their implementation regarding the development of the health care sector in Poland, with particular emphasis on problem areas related to, m.in others, improvement of the quality of health care, computerization and cybersecurity in the area of health care, development of innovative activities in health care, providing medical entities with (additional) financial sources and activities related to the occurrence of the epidemic COVID-19. The originality of the study results from the analysis and evaluation of management control in the area of implementation of objectives and tasks for health care, with the presentation of changes in the structure of tasks, achieved values of indicators (determining the degree of task implementation) and proposals for solutions to improve management control.
Keywords: audit committee; management control; internal audit